Ca2+ Signaling in Cardiac Fibroblasts: An Emerging Signaling Pathway Driving Fibrotic Remodeling in Cardiac Disorders - Francesco Moccia; Antonio Totaro; Germano Guerra; Gianluca Testa (Biomedicines)
Cardiac fibrosis is a scarring event that occurs in the myocardium in response to multiple cardiovascular disorders, such as acute myocardial infarction (AMI), ischemic cardiomyopathy, dilated cardiomyopathy, hypertensive heart disease, inflammatory heart disease, diabetic cardiomyopathy, and aortic stenosis. Fibrotic remodeling is mainly sustained by the differentiation of fibroblasts into myofibroblasts, which synthesize and secrete most of the extracellular matrix (ECM) proteins. An increase in the intracellular Ca2+ concentration ([Ca2+]i) in cardiac fibroblasts is emerging as a critical mediator of the fibrogenic signaling cascade. Herein, we review the mechanisms that may shape intracellular Ca2+ signals involved in fibroblast transdifferentiation into myofibroblasts. We focus our attention on the functional interplay between inositol-1,4,5-trisphosphate (InsP3) receptors (InsP3Rs) and store-operated Ca2+ entry (SOCE). In accordance with this, InsP3Rs and SOCE drive the Ca2+ response elicited by Gq-protein coupled receptors (GqPCRs) that promote fibrotic remodeling. Then, we describe the additional mechanisms that sustain extracellular Ca2+ entry, including receptor-operated Ca2+ entry (ROCE), P2X receptors, Transient Receptor Potential (TRP) channels, and Piezo1 channels. In parallel, we discuss the pharmacological manipulation of the Ca2+ handling machinery as a promising approach to mitigate or reverse fibrotic remodeling in cardiac disorders.